Current challenges in monitoring, discrimination, and management of induced seismicity related to underground industrial activities: A European perspective. (18th April 2017) - Grigoli, Francesco; Cesca, Simone; Priolo, Enrico; Rinaldi, Antonio Pio; Clinton, John F.; Stabile, Tony A.; Dost, Bernard; Fernandez, Mariano Garcia; Wiemer, Stefan; Dahm, Torsten
Abstract: Due to the deep socioeconomic implications, induced seismicity is a timely and increasingly relevant topic of interest for the general public. Cases of induced seismicity have a global distribution and involve a large number of industrial operations, with many documented cases from as far back to the beginning of the twentieth century. However, the sparse and fragmented documentation available makes it difficult to have a clear picture on our understanding of the physical phenomenon and consequently in our ability to mitigate the risk associated with induced seismicity. This review presents a unified and concise summary of the still open questions related to monitoring, discrimination, and management of induced seismicity in the European context and, when possible, provides potential answers. We further discuss selected critical European cases of induced seismicity, which led to the suspension or reduction of the related industrial activities. Key Points: We provide a unified and concise summary about the still open questions on monitoring, discrimination, and management of induced seismicity We review critical cases of induced seismicity in Europe which led to the suspension of the related industrial activities This study outlines the scientific and societal challenges posed by the induced seismicity in a European perspective